Pengaruh Penggunaan Media Pembelajaran Berbasis Video pada Mata Pelajaran Pendidikan Kewarganegaraan - Deli, Deli; Marlon, Richie (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2022)
Education is one of most important aspect in life. Civic Studies become of most important subjects. Based on short interview at Dharma Maitreya Junior High School, some students reveal about Civic Studies learning process, still seems boring. The purpose of this research is to find out the effectiveness of video learning media based animation, can help increase student interest in learning, especially in Civic Studies subjects. Data collection techniques in this research is used Experiment method, Qualitative method, and Quantitative method, and making the work agendas and work by using method Multimedia Development Life Cycle (MDLC). The result of this research showed that, there is does not have significant effect between of video learning media based animation with increase student interest in learning, especially in Civic Studies subject. It can be concluded based on the result of hypothesis testing using Independent Samples T-Test. The results of the analysis show that the value of sig (2-tailed) bigger then the level of significance or 0,557 0,05, that means it is the rejection of H0, and Ha received.